De la adaptación a la transformación en Colombia: las competencias clave para los profesionales en la era de la Inteligencia Artificial. - Sánchez Aristizábal, Camilo Andrés; Londoño Romero, María Gabriela; Chiquiza Limas, Mateo; Castañeda Alonso, Diana Shirley (Fondo Editorial Universidad Antonio Nariño, 2024)
Artificial Intelligences (AI) are computer systems that have the ability to mimic activities performed by a human being, functioning through algorithms. AI in Colombia operates within an ethical framework. This technology is constantly growing, making it difficult to predict with certainty which professions will be replaced. However, it is expected to have a significant impact on many sectors. Consequently, discussions are beginning on the skills that individuals need to possess in order to be competent in relation to new professional profiles, reflecting a clear understanding that the labor market is constantly evolving and that future jobs will require different competencies than traditional ones.